Synchrony, Co‐Eating and Communication During Complementary Feeding in Early Infancy. (10th November 2017) - Costantini, Cristina; Akehurst, Lucy; Reddy, Vasudevi; Fasulo, Alessandra
Abstract : The transition from milk to complementary food is a crucial but difficult process, requiring considerable adult sensitivity. We know little about the relationship between maternal feeding behaviors and infant willingness to eat at the onset of complementary feeding (CF), and we know even less about how these patterns might vary across cultures. Thirty‐seven dyads (15 from the UK and 22 from Italy) took part in a longitudinal study, during which mealtimes were video‐recorded 1 week after the onset of CF (Time 1) and at 7 months of infant age (Time 2). The first five minutes of mealtimes were coded for maternal feeding behaviors, for infant willingness to eat, and for synchrony in feeding. Maternal vocal communications (MVCs) and attention‐directing acts (ADAs) during the whole mealtime were also coded. Infant willingness to eat was significantly related to synchrony and co‐eating, suggesting the importance of sensitivity and empathy during feeding as in other parent–infant interactions. The frequency of maternal ADAs varied between nationalities and, contrary to current advice, did not relate negatively to infant willingness to eat. These patterns and variations suggest the need to consider CF as a contextually variable and sensitive foundation for feeding relationships.